On the factors and the degree of their effect on subglacial melt and changes in the state of Antarctic subglacial lakes - Alina Boronina; Sergey Popov; Gang Qiao (Arctic, Antarctic, and Alpine Research)
This study presents the results of mathematical modeling of the degree of effects of various characteristics on basal conditions in Antarctica. The model is based on the numerical solution of the one-dimensional Stefan problem. Five factors determining the nature of subglacial processes have been studied: ice thickness, snow-firn thickness, surface mass balance, air temperature, and geothermal heat flux. It was found that on the Antarctic plateau, slope, and coast, the geothermal heat flux has the greatest influence on the basal conditions. It is the heat flux that is responsible for the transition of most Antarctic lakes from a stable state to an active one (except for the ice stream regions). In areas where the ice sheet is thinner than 1,500 m, air temperature is the second most important factor affecting subglacial conditions. In areas where the glacier is thicker, the ice thickness begins to have a greater effect. The snow-firn thickness and snow accumulation have little effect on subglacial melt in most parts of Antarctica. Calculations over a 100-year period show that if meltwater accumulates on the bedrock rather than being completely channeled, it leads to a decrease in the average rate of subglacial melting by approximately 10 times.